Leaf area, spray volumes and applicable quantities of fungicide during the protection period for control of Asian soybean rust - Chechi,Amanda (2018)
ABSTRACT The purpose of this study was to check the influence of leaf area index, spray volumes and applicable quantities of fungicide during the protection period, and for control of Asian soybean rust. All tests were conducted in the field and in the laboratory between 2014 and 2016. The quantity of fungicide and the spray volume were varied in the application of fungicides on soybean plants with different leaf area index. Rainfall simulation tests were also carried out at different times after application of fungicide. The spray volume and application rate of fungicide should be adequately proportioned according to the leaf area index of the soybean cultivar. The closer to the time of application that the rain occurs, the lower the control obtained by applying the fungicide. The leaf area index, the fungicide application rates, and the spray volumes influenced the protection period of fungicides and the control of Asian soybean rust.